تاريخ الفكر الاقتصادي في الحضارات القديمة - شاهد, الياس; بالي, حمزة (جامعة الوادي - University of Eloued, 2016)
تهدف هذه الدراسة إلى استعراض عملية تطور الأفكار الاقتصادية عبر الحضارات القديمة بطريقة أكاديمية وبأسلوب واضح، لكي يساعد على تطوير فهمنا للاقتصاد المعاصر، ويوفر لنا وجهة نظر في فهم الأفكار الاقتصادية للمدارس الفكرية المختلفة، وتركز على أبرز المساهمات والأفكار لما لها من أهمية. وتجدر الإشارة إلى أن دراسة تاريخ الاقتصاد تستمر في النمو والتطور وذلك مع نضوج علم الاقتصاد ذاته. فالأفكار الجديدة والشواهد الجديدة والمشكلات الجديدة والفهم الجديد يدعو إلى إعادة النظر حول المساهمات والخلافات والأفكار التي ظهرت في الماضي, والتي ولدت مع ولادة الحضارات القديمة كالإغريقية، والرومانية والصينية والفارسية والحضارة العربية. Abstract : economic ideas through ancient civilizations in an academic way and in a clear way to help develop our understanding of the modern economy. It provides us with a view to understanding the economic ideas of the various schools of thought and focuses on the most important contributions and ideas because of their importance. It should be noted that the study of the history of the economy continues to grow and develop with the maturity of economics itself. New ideas, new evidence, new problems and new understanding call for a reconsideration of the contributions, controversies and ideas of the past that were born with the birth of ancient civilizations such as Greek, Roman, Chinese, Persian and Arab c
مقال
Keywords: الفكر الاقتصادي, تاريخ الاقتصاد, الحضارة الإغريقية, الحضارة الرومانية; economic thought, history of the economy, Greek civilization, Roman civilization